Complete Cystic Degeneration of a Uterine Myoma Posing a Diagnostic Dilemma - Abdi Dandena Dibaba; Neema Ljani; Aqeela Mustafa; Hussein Khanbhai; Abel Ntungi; Alfred Secha; Natnael Alemu Bezabih; Misiker Gebremariam Waktola; Shafi Samiji Ramadhani (Case Reports in Radiology)
In this case, we describe a rare presentation of a uterine myoma in a 42-year-old female patient who presented with a progressively enlarging abdominopelvic mass and heavy menstrual bleeding for 1 month. Initial work showed that the patient has a low hemoglobin count and elevated CA-125 tumor marker. A pelvic ultrasound revealed a cystic pelvic lesion with an undetermined origin. Subsequent follow-up after 6 weeks showed significant enlargement of the mass, prompting a pelvic MRI to be performed; the MRI showed a large, completely cystic uterine myoma arising from the anterior myometrium. This case highlights the atypical presentation of a common gynecological condition that can result in a diagnostic dilemma and the importance of advanced imaging such as MRI to be a problem-solving tool.